1977
DOI: 10.1111/j.1365-2672.1977.tb00683.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonellae on Chilled and Deep Frozen Broiler Carcasses by Irradiation

Abstract: Chilled and deep‐frozen broiler carcasses were examined for total counts of salmonellae using pooled samples taken from 76 batches each of five birds. By means of a most probable number technique (MPN) it was found that counts expressed/100 g of skin or /500 ml of thaw water varied between < 2 and 1400 with 90% being < 100. Irradiation of carcasses using a dose of 250 krad was found to be highly effective in destroying salmonellae whether the birds had been chilled or deep‐frozen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 11 publications
1
18
0
1
Order By: Relevance
“…The finding that Sulmonellae were destroyed by a relatively low dose irradiation confirmed previous research. Mulder et al (1977), Bok and Holzapfel (1984) and Dickerson et al (1991) demonstrated that irradiation (2-3 kGy) effectively destroyed all Salmonellae on chicken. Klinger et al (1986) reported complete elimination of SuZmonellue on broiler carcasses irradiated up to 4.5 kGy and stored at 4°C.…”
Section: Resultsmentioning
confidence: 96%
“…The finding that Sulmonellae were destroyed by a relatively low dose irradiation confirmed previous research. Mulder et al (1977), Bok and Holzapfel (1984) and Dickerson et al (1991) demonstrated that irradiation (2-3 kGy) effectively destroyed all Salmonellae on chicken. Klinger et al (1986) reported complete elimination of SuZmonellue on broiler carcasses irradiated up to 4.5 kGy and stored at 4°C.…”
Section: Resultsmentioning
confidence: 96%
“…0.37 kGy in 320 poultry meat (Mulder et al, 1977) or 0.41 kGy in dry fermented sausages (Cabeza et al, 2009). 321…”
Section: Optimization Of the Radiation Process 283mentioning
confidence: 99%
“…Gamma irradiation has been employed for decontamination and/or sterilization of dehydrated vegetables (Zhou, Jin, Wei, Fu, & Xiong, 1996), fruits (Yu, Zhang, Cheng, & Zheng, 1993;Zhang, Liu, Li, Yang, & Tian, 1993), seasonings (Chen, Xu, Chen, Chen, & Dong, 1993) and animal foods (Chwla et al, 2003;Fu, Shen, Bao, & Chen, 2000;Kamat, Warke, Kamat, & Thomas, 2000;Mahrour, Caillet, Nketsa-Tabiri, & Lacroix, 2003;Yang, Perng, Liou, & Wu, 1993) and then to prolong the storage period of irradiated food. There is ample published evidence showing the enormous potential of this method for extending shelf life of chicken meat by eliminating certain spoilage and pathogenic organisms (Mulder, Notermans, & Kampelmacher, 1977;Thayer, Lachica, Huhtanen, & Wierbicki, 1986;Urbain, 1989;WHO, 1988). Many researchers recognized and reported that gamma irradiation in low doses, below 10 kGy; kill most organisms without deterioration of food quality (Lacroix et al, 1991;Mulder, 1982;Olson, 1998;Thayer, Boyd, Fox, Lakritz, & Hamson, 1995).…”
Section: Introductionmentioning
confidence: 97%